2023
DOI: 10.1101/2023.09.25.559330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White matter tract microstructure, macrostructure, and associated cortical gray matter morphology across the lifespan

Kurt G Schilling,
Jordan A. Chad,
Maxime Chamberland
et al.

Abstract: Characterizing how, when and where the human brain changes across the lifespan is fundamental to our understanding of developmental processes of childhood and adolescence, degenerative processes of aging, and divergence from normal patterns in disease and disorders. We aimed to provide detailed descriptions of white matter pathways across the lifespan by thoroughly characterizing white mattermicrostructure, white mattermacrostructure, and morphology of thecortexassociated with white matter pathways. We analyze… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
(154 reference statements)
1
1
0
Order By: Relevance
“…(Qualitative comparisons of GM and WM degeneration or correlations of GM atrophy with voxelwise WM microstructure metrics are more common). However, one recent study based on connectomic imaging from 2,789 datasets (Schilling et al, 2023) reported correlations of similar magnitude between FA and cortical thickness in older adults, in line with the current findings. The relatively modest association between GM and WM degeneration may indicate that both GM atrophy and WM degeneration are driven not only by some common processes but also tissue-specific factors.…”
Section: Associations Between Grey and White Matter Degenerationsupporting
confidence: 91%
“…(Qualitative comparisons of GM and WM degeneration or correlations of GM atrophy with voxelwise WM microstructure metrics are more common). However, one recent study based on connectomic imaging from 2,789 datasets (Schilling et al, 2023) reported correlations of similar magnitude between FA and cortical thickness in older adults, in line with the current findings. The relatively modest association between GM and WM degeneration may indicate that both GM atrophy and WM degeneration are driven not only by some common processes but also tissue-specific factors.…”
Section: Associations Between Grey and White Matter Degenerationsupporting
confidence: 91%
“…[11] found heterogeneous patterns of age-related macrostructural changes in the brain WM compared to the more homogeneous patterns of microstructural changes. In another study, the same authors reported synchronous micro- and macro-structural changes across the human lifespan [12]. Combining DTI, connectivity and tract shape measures (length, diameter and elongation) derived with a fusion prediction network, Liu et al .…”
Section: Introductionmentioning
confidence: 99%